Attosecond Pulse Generation and Measurement - Nandy, Biplob (IISER-M, 2016)
The first part of this thesis deals with the three-step model of High Harmonic Generation using Femtosecond pulses and we will begin with a brief discussion of the model and the theory behind the phenomenon. The second and the major part of this thesis deals with the experi- mental techniques and the setup (including the Ultra-High vacuum and associated components) required and used by us for generating Attosec- ond pulses in the EUV region. We will also discuss in detail the methods used for the beam alignment and the procedure to obtain "Femtosecond Time Zero" using a modified "Mach-Zehnder Interferometer setup". The third and final part of this thesis deals with the detection and measurement of Attosecond pulses using various techniques and the prin- ciple behind the same. We will also discuss in detail regarding the working principle of a "Micro-Channel Plate detector".
Keywords: Physics; High Harmonic Generation; Femtosecond pulses; Attosecond pulses